The Use of Surgical Splints in Orthognathic Surgery: A Bibliometric Study - Francisco Samuel Rodrigues Carvalho; Déborah Isis de Oliveira Barbosa; Iara Furtado Torquato; André Mattos Britto de Souza; Roberta Dalcico; Filipe Nobre Chaves; Fábio Wildson Gurgel Costa (Indian Journal of Plastic Surgery)
Introduction Orthognathic surgeries require the use of surgical splints (SS) to stabilize the occlusion and the segments fixed with plates and screws. Technological advances in the field of computing and the possibility of generating three-dimensional (3D) images have brought different possibilities for making SS, which has generated greater predictability and customization of surgical plans. The bibliometric study can have a qualitative character through the scope of articles in a certain area of knowledge. It is a selection process that can track a topic or scientific production. Methods The present study aimed to carry out a bibliometric literature review, in order to assess the evolution of the use of SS and the different planning protocols in orthognathic surgery. The Scopus database was used, with the terms “splint” and “orthognathic surgery.” Results A total of 331 articles were found. These were exported to Rayyan for application of the inclusion and exclusion criteria and selection of articles. A total of 76 references were selected and exported to the VOSviewer application for the analysis of bibliometric data. Conclusions Orthognathic surgery was initially not associated with any computerized technological resource; however, it underwent updates between the years 2010 to 2012. These advances allowed surgical planning to become faster, cheaper, and more accurate.